STUDY OF BINDING INTERACTIONS OF HUMAN CARBONIC ANHYDRASE XII - Barua, Harsh; Bhagat, Nidhi; Toraskar, (mrs.) M. P. (International Journal of Current Pharmaceutical Research, 2016)
Objective: The present study was carried out to study the binding interactions of different N'-(substituted phenyl sulfonyl)-pyridine-2-carbohydrazide derivatives and N'-(substituted phenyl sulfonyl)-thiophene-2-carbohydrazide derivatives which were synthesized by senior students from research laboratory, with objective to explore the suitability of selected ligands for their binding affinity for the selected target. Methods: Binding interactions of the selected ligands were studied using glide module of Schrodinger software using Maestro 10.1 interface. At the end of molecular docking studies, docking scores along with 2D and 3D binding interactions of these ligands were studied to evaluate the potency of ligands to act as selective human carbonic anhydrase (hCAXII) inhibitors in comparison with standard inhibitor Acetazolamide (AZA). Results: Docking study on the ligands exhibited very similar conformation and binding interactions with hCAXII as that of standard. This suggests that selected ligands might possess significant binding affinity for hCAXII. Conclusion: It can be concluded that the selected ligands have the potential to act as inhibitors of hCAXII.